2005
DOI: 10.1167/iovs.04-0978
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Substances on the Biomechanical Behavior of Lamina Cribrosa and Peripapillary Sclera

Abstract: Glyceraldehyde and methylglyoxal increase the stiffness of the LC and of the ppSc in human and in porcine eyes. These substances induce changes in the extracellular matrix according to the Maillard reaction as it occurs during the ageing process or in case of high blood glucose levels. Collagenase reduces the stiffness of the tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 44 publications
5
65
1
4
Order By: Relevance
“…This behavior is in line with the findings from the uniaxial tensile strip tests in which the sclera was shown to have a higher tangent modulus when stressed. [23][24][25] The scleral tangent modulus measured in this study (Ej IOP ¼ 0.20 MPa at 15 mm Hg) was approximately twice that of the corneal tangent modulus measured in our previous study (Ej IOP ¼ 0.12 MPa at 15 mm Hg) using the same indentation technique. 20 This suggested that the sclera is stiffer than the cornea, providing key structural support to the eye.…”
Section: Discussionsupporting
confidence: 63%
“…This behavior is in line with the findings from the uniaxial tensile strip tests in which the sclera was shown to have a higher tangent modulus when stressed. [23][24][25] The scleral tangent modulus measured in this study (Ej IOP ¼ 0.20 MPa at 15 mm Hg) was approximately twice that of the corneal tangent modulus measured in our previous study (Ej IOP ¼ 0.12 MPa at 15 mm Hg) using the same indentation technique. 20 This suggested that the sclera is stiffer than the cornea, providing key structural support to the eye.…”
Section: Discussionsupporting
confidence: 63%
“…Stress-strain measurements were performed according to standard protocols [17] . Briefly, strips were clamped horizontally with a distance of 3 mm between the clamps of the microcomput- To precondition the strips, stress-strain measurements were performed with a prestress of 10 !…”
Section: Stress-strain Measurementsmentioning
confidence: 99%
“…AGEs were identified in diabetic or ageing ocular tissues including cornea [10] , lens [11] , vitreous [12] , and retina [13] but also in the optic nerve head (ONH) [14][15][16] . Interestingly, a recent in vitro study detected a significant stiffening of the lamina cribrosa and the peripapillary sclera (ppSc) under the influence of AGE metabolites in human and porcine eyes, indicating glucose-related cross-linking effects of AGEs [17] . As changes in biomechanical properties of the ONH and the ppSc are particularly relevant to glaucomatous optic nerve damage [18,19] and since AGE levels have been shown to be significantly higher in diabetics compared to age-matched controls [20] , it is not unreasonable to propose that biomechanical properties of the ONH tissues in diabetics may also be affected.…”
mentioning
confidence: 99%
“…However, these values are inconsistent among different authors and vary by up to 100-fold for sclera and 1000-fold for cornea. 5,[9][10][11][12][13][14] Few studies have described the compressive elastic moduli of the sclera and cornea. 15 The insertion of needles into soft tissues has been published by several investigators.…”
Section: Introductionmentioning
confidence: 99%